(untitled) (Progressive Agriculture, 2014)
Mesta (Hibiscus sabdariffa) is one of the important fibre crops having worldwide acceptance. The crop was found to susceptible to a number of seed and seedling disease causal pathogens; most of them were seed-borne in nature. Germination of seeds and seed-borne fungi were recorded using standard blotter method which varied significantly among different treatments ranged from 84% to 97.33%. The highest (97.33%) germination was found in case seed washed with water and then treated with garlic extract (1 : 1) and washing of seeds with water followed by treating with Knowin 50 WP. Nine different fungi were detected in samples of mesta seeds in using standard blotter method. The fungi were Macrophomina phaseolina, Botryodiplodia theobromae, Colletotrichum corchori, Curvularia lunata, Fusarium spp., Aspergillus favus, A. niger, Penicillium spp. and Alternaria spp. The finding of the study revealed that seed washing with water followed by seed treatment with garlic extract (1 : 1) or Knowin 50 WP (0.2%) resulted significant reduction of seed-borne fungal population and enhancing seeding vigor. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.18424 Progress. Agric. 24(1&2): 1 - 7, 2013